2003
DOI: 10.3758/bf03195813
|View full text |Cite
|
Sign up to set email alerts
|

Situation-evoking stimuli, domain of reference, and the incremental interpretation of lexical ambiguity

Abstract: In two experiments, we examined the influence of situation-evoking stimuli on the resolution of lexical ambiguity. In Experiment 1, we examined situation-evoking stimuli at an early NP position. Readers were asked to establish whether specific entities were likely to participate as agents in contextually defined situations. Naming latencies demonstrated that defined situations headed by likely agents evoked a domain of reference that included only the situation-appropriate meaning of a targeted lexical ambigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 68 publications
2
18
0
1
Order By: Relevance
“…This view is broadly consistent with those of researchers who have stressed the role of situation models in language comprehension (e.g., Potts, Keenan, & Golding, 1988;Vu, Kellas, Petersen, & Metcalf, 2003). The interaction of lexical and world knowledge also is consistent with the view of thematic roles developed recently by McRae and colleagues (Ferretti, McRae, & Hatherell, 2001;McRae et al, 1997), who proposed that thematic role assignment involves detailed experiential knowledge that is highly specific to events denoted by individual verbs.…”
Section: Expectancy Generation and Event Knowledgesupporting
confidence: 89%
“…This view is broadly consistent with those of researchers who have stressed the role of situation models in language comprehension (e.g., Potts, Keenan, & Golding, 1988;Vu, Kellas, Petersen, & Metcalf, 2003). The interaction of lexical and world knowledge also is consistent with the view of thematic roles developed recently by McRae and colleagues (Ferretti, McRae, & Hatherell, 2001;McRae et al, 1997), who proposed that thematic role assignment involves detailed experiential knowledge that is highly specific to events denoted by individual verbs.…”
Section: Expectancy Generation and Event Knowledgesupporting
confidence: 89%
“…In contrast to the eye movement studies on the subordinatebias effect, Kellas, Vu, and colleagues (Kellas, Martin, Yehling, Herman, & Vu, 1995;Martin, Vu, Kellas, & Metcalf, 1999;Vu, Kellas, Metcalf, Herman, 2000;Vu, Kellas, Petersen, & Metcalf, 2003) provided evidence in support of selective access to contextually appropriate meanings for ambiguous words. Using word-by-word self-paced reading and probe methodologies, they found that strong context could modulate the subordinate-bias effect; the effect was present when weak context was used, but was eliminated in the presence of strong context.…”
Section: Introductionmentioning
confidence: 80%
“…presence or absence of a biasing context), it was possible that our preceding disambiguating story context would influence the pattern of results. Biasing context has been found to influence the processing of ambiguous lexical items (Rayner et al, 1999;Vu et al, 2003). In their discussion of the 'reordered access model' of lexical access, Rayner et al (1999) hold that context can potentially boost the activation of the less frequent meaning of an ambiguous word such that it becomes available to interpretive processes before the more frequent meaning.…”
Section: Hypotheses and Predictionsmentioning
confidence: 99%